Dampak Komentar Negatif dalam Akun Media Sosial bagi Perkembangan Karakter Anak Usia Dini - Rd Bily Parancika; Mohammad Aris (LPPM STKIP PGRI Bandar Lampung, 2023)
Character education aims to develop children's habits and behavior that are commendable and in line with universal values ​​and religious national cultural traditions. If efforts to trap these characters are not accompanied by parental supervision of things or information that children get through social media, then it can have an impact on the habits and behavior of children at a later age if too many negative thinking concepts are obtained when accessing social media. These impacts not only affect children's behavior, but also children's language and communication skills. Thus this research is expected to be able to give a stigma to readers about how dangerous negative comments are for early childhood. This study uses a qualitative approach. The method used is narrative content analysis through several stages, including observation, literature study, and documentation. The research results are presented in the form of a qualitative description. The results of the study show the impact of negative comments on the character development of early childhood.